Microbial lipases: An overview of screening, production and purification. (November 2019) - Bharathi, Devaraj; Rajalakshmi, G.
Abstract: Lipases are industrially important biocatalyst, particularly microbial lipases and therefore, screening, production and purification of lipase enzyme from microbial strains are continuously emerging to fulfil the needs of pharmaceutical and food industries. More recently, various cost effective and efficient approaches are being attempted to increase the production of lipases in microbial strains. In this junction, this article attempt to connect production of lipases using various microbial strains such as bacteria, fungi and yeast has been highlighted and discussed, in order to enable researchers to choose an appropriate strains for lipase production. Then, screening of lipase producer and production of lipases under different fermentation system was discussed. Later, impact of various factors such as carbon sources, nitrogen sources, pH and temperature has been assessed, and presented in the perspective of increasing its production from microbial strains. Finally, purification techniques for lipase enzymes was summarized and recent literature pertaining to lipase purification from microbial stains are reviewed, and summarized. Highlights: Lipases from microbial origin are much embraced owing to their high bio catalytic activity. Different methods of lipase screening have been reviewed. Economical production strategies for the lipases are reviewed in this work.